Bacterial urinary tract infection and antibiotic sensitivity pattern among type II diabetic patients – A cross-sectional study from tertiary care teaching hospital in Central Lahore (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACTBackground: Diabetes mellitus is the fifth leading cause of death in developed countries.Risk of infections is increased in diabetic patients with urinary tract being the most common site of infection. Worldwide, the prevalence of urinary tract infections (UTI) is estimated to be around 150 million persons per year . UTI exhibit a poorer prognosis in patients of type 2 diabetes mellitus (T2DM) due to a compromise in their immune status in addition to emerging antimicrobial resistance due to widespread use of antimicrobial agents. This study aims to determine frequency of common bacterial pathogens causing UTI and antibiotic sensitivity pattern among type 2 diabetic patients. This may help to guide physicians regarding appropriate management of UTI in the local population to avoid multidrug resistance.Patients and Methods: This cross sectional study involved 215 type 2 diabetic patients admitted to Medical Unit-III of Sir Ganga Ram hospital, Lahore from 01-12-2016 to 31-05-2017. Type 2 adult diabetic patients (diagnosed for at least 1 year) of age 40-80 years, either male or female , with urine pus cells ≥5/HPF performed as baseline investigation at admission were included in the study. Further urine samples were obtained (clean catch midstream urine 10cc in two wide mouth sterile screw capped plastic jars) before starting treatment. Samples were sent for microscopy and culture. Culture results and antibiotic sensitivities were recorded. Data was analyzed using SPSS for windows version 23.0. Categorical variables like gender, organisms and antibiotic sensitivitywas presented in Frequency or Percentage form. Numerical variables like age and duration of diabetes were presented as Mean± SD. Data was stratified for age, gender and duration of DM to deal with effect modifiers. Post stratification chi-square test was applied. P-value of ≤0.05 was considered significant.Results: Total of 215 patients were included. Mean age was 63.76±10.342 years of which 164 (76.3%) were females, while 51 (23.7%) were males reflecting female predominance.Most common isolated organism in urine culture was E.coli (58.6%), followed by Klebsiella (20.5%), Proteus(9.3%), Pseudomonas(8.4%) and Enterococcus (3.3%)species.Most of the patients (76.7%) were sensitive to piperacillin-tazobactam followed bycarbapenems (67%) and Gentamycin(56.7%), whereas 24.2% showed sensitivity to all antibiotics.Conclusion: Females are most commonly affected among diabetic patients. The commonest isolate was E.coli among culture positive UTIs. E.coli was most sensitive to piperacillin-tazobactam and carbapenems followed by Gentamycin while least sensitive to Ceftriaxone.The results emphasize the importance of practcse of urine culture and sensitivity testing in diabetic patients and cautious approach to use of commonly used antibiotic ceftriaxone and ciprofloxacin as empirical treatment for UTI despite the low sensitivityof the drug to the most prevailing organism.
Keywords: Urinary tract infection, Type2 Diabetes Mellitus, Antibiotic sensitivity, Pathogens